A RECONFIGURABLE METASURFACE IN THE FORM OF A FABRY-PÉROT RESONATOR, INVOLVING SEMI-TRANSPARENT MIRRORS AND A NONLINEAR DIELECTRIC INSERT - Ye. O. Antonenko; Yu. V. Antonenko; A. V. Gribovsky; V. A. Katrich (Radio physics and radio astronomy (Print), 2024)
Subject and Purpose. The paper is aimed at suggesting ways for implementing electromagnetic devices that would involve a nonlinear dielectric inside the structure for concentrating electromagnetic field within it at relatively low intensities of the excitation field. A representative example is offered by a Fabry-Pérot resonator with semi-transparent mirrors and a nonlinear dielectric inside. Methods and Methodology. The paper presents a fundamentally new approach to controlling the frequency response of a metasurface, and a method for protecting electronic modules from high excitation powers. The method is based on the use of nonlinear properties of a Fabry-Pérot "resonator-capacitor" containing a nonlinear dielectric in its volume. Thus, we propose a method for creating spatial filters and antenna protecting fairings capable of active reconfiguration. Results. Analysis of the results has shown that by changing the voltage across the resonator-capacitor plates it is possible to control the degree of electromagnetic field localization in the resonator volume. The frequency response of the metasurface based on the Fabry-Pérot resonator with a nonlinear dielectric inside can be reconfigured by changing the voltage applied to the resonator mirrors. The advantages provided by electrical control of the frequency-selective characteristics include an increased efficiency and possibility of integrating digitally controllable systems into antennas. Conclusions. The use of a Fabry-Pérot "resonator-capacitor"model, with a nonlinear dielectric inside, in the capacity of a reconfigurable metasurface, else as a power limiter in a variety of devices, has sufficient prospects for application in microwave transmitting systems. A special area of application for the reconfigurable Fabry-Pérot resonators is creation of broadband receive antenna systems for direction- finding. In essence, the proposed Fabry-Pérot resonator is a reflective antenna array with an ability to exhibit, conceal or alter its electrodynamic properties according to a certain algorithm. This opens up prospects for its application in "friend-or-foe" recognition systems, reflective beacons, navigation systems, etc.